AC927, a σ Receptor Ligand, Blocks Methamphetamine-Induced Release of Dopamine and Generation of Reactive Oxygen Species in NG108-15 Cells - Kaushal, Nidhi (The American Society for Pharmacology and Experimental Therapeutics, 2012)
Methamphetamine is a highly addictive psychostimulant drug of abuse that causes neurotoxicity with high or repeated dosing. Earlier studies demonstrated the ability of the selective σ receptor ligand N-phenethylpiperidine oxalate (AC927) to attenuate the neurotoxic effects of methamphetamine in vivo. However, the precise mechanisms through which AC927 conveys its protective effects remain to be determined. With the use of differentiated NG108-15 cells as a model system, the effects of methamphetamine on neurotoxic endpoints and mediators such as apoptosis, necrosis, generation of reactive oxygen species (ROS) and reactive nitrogen species (RNS), and dopamine release were examined in the absence and presence of AC927. Methamphetamine at physiologically relevant micromolar concentrations caused apoptosis in NG108-15 cells. At higher concentrations of methamphetamine, necrotic cell death was observed. At earlier time points, methamphetamine caused ROS/RNS generation, which was detected with the fluorigenic substrate 5-(and-6)-chloromethyl-2′,7′-dichlorodihydrofluorescin diacetate, acetyl ester, in a concentration- and time-dependent manner. N-Acetylcysteine, catalase, and l-N(G)-monomethyl arginine citrate inhibited the ROS/RNS fluorescence signal induced by methamphetamine, which suggests the formation of hydrogen peroxide and RNS. Exposure to methamphetamine also stimulated the release of dopamine from NG108-15 cells into the culture medium. AC927 attenuated methamphetamine-induced apoptosis, necrosis, ROS/RNS generation, and dopamine release in NG108-15 cells. Together, the data suggest that modulation of σ receptors can mitigate methamphetamine-induced cytotoxicity, ROS/RNS generation, and dopamine release in cultured cells.